Perceptions of Undergraduate Students Regarding the Inclusion of Clinical Audit in their Curriculum - Dilnawaz, Mansoor; Kanwal, Ayesha; Saeed, Hajra; Mansoor, Taha; Mansoor, Madha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find out undergraduate students’ perceptions regarding the inclusion of clinical audits in their curriculum. Study Design: Exploratory sequential mixed methods study. Place and Duration of study: Combined Military Hospital, Lahore Pakistan, from Dec 2022 to Mar 2023. Methodology: The first phase of the study comprised a quantitative research questionnaire regarding undergraduate students’ perceptions about the inclusion of a clinical audit in their curriculum. These perceptions were explored in depth in the second phase with focus group discussions (FGD). Thirty students participated in the study, ten from the fourth year and twenty from the final year MBBS. Results: The study included 30 participants. The results showed that (24, 80%) of participants were able to develop skills as team members, (22, 73%) were able to identify audit topics, collect data, write audit reports and understand conflicts of interest, and (21, 70%) were able to write audit proposal and develop skill in life long audit learning. The key themes emerging from clinical audit focus group discussions (FGD) were better clinical care, patient safety, lack of understanding about audit by students and faculty and improper implementation mechanisms. Conclusion: In conclusion, a clinical audit promotes a safe, good-quality, and evidence-based environment for patient care. It also decreases the risk of clinical negligence and should be incorporated as an integral part of the undergraduate curriculum.